Evaluation of an enzymatic Chlamydia trachomatis point-of-care rapid assay in Rwanda: the BioChekSwab Rapid Test. (16th October 2015) - De Baetselier, Irith; Mwambarangwe, Lambert; Cuylaerts, Vicky; Musengamana, Viateur; Agaba, Stephen; Kestelyn, Evelyne; van de Wijgert, Janneke; Crucitti, Tania
Abstract : Objectives: We evaluated the performance of an enzymatic point-of-care rapid test for Chlamydia trachomatis (CT) (the BioChekSwab CT Rapid Test, EnZtek Diagnostics, Rio Vista, California, USA), which detects CT's Peptidase 123CBV enzyme and provides a result 15 min after specimen collection. Methods: Two endocervical swabs, including one BioChekSwab, per person were obtained from 137 women who participated in a reproductive health study in Rwanda. The BioChekSwab was processed according to the manufacturer's instructions. A substrate was squirted over the swab by the study physician immediately after collection, and another reagent was released over the swab tip at arrival in the laboratory. The test was considered positive if a blue colour developed within 2 min. The other regular flocked endocervical swab was processed at the Institute of Tropical Medicine (ITM), Belgium, using a testing algorithm: Abbott RealTime CT/ Neisseria gonorrhoeae (NG) assay with the confirmation of positive results by an in-house real-time PCR assay. Results: Of the 137 women, nine were CT positive by the testing algorithm. All nine positive results were missed by the BioChekSwab assay and four false-positive results were obtained. The sensitivity was therefore 0% (95% CI 0% to 33.6%) and the specificity was 96.9% (95% CI 92.2% to 99.1%). Conclusions: The BioChekSwab Rapid Test, although ISO13485 certified and Conformitée Européenne (CE) labelled, lacked any sensitivity in our setting.